Influence of Purposeful Activities on Upper Extremity Motor Performance: A Systematic Review. (October 2020) - Collis, Julie M.; Signal, Nada; Mayland, Elizabeth; Wright-St Clair, Valerie A.
Following upper extremity injury, exercise-approaches are commonly used to address motor impairments. Occupation-based approaches are also used but less widely promoted and their mechanisms of action not well-understood. Movement performed during purposeful activities and occupations may yield better motor performance than during nonpurposeful tasks. This review investigated the influence of engagement in purposeful activities and occupations on upper extremity motor performance in healthy and musculoskeletal populations. Databases were searched for studies in healthy or upper extremity musculoskeletal–injured adults that compared motor performance during purposeful activities against nonpurposeful movements. Twenty-one studies of moderate quality, conducted predominantly in healthy populations, were included. Upper extremity movement quantity and quality were enhanced when performed during purposeful conditions. Purposeful activities have potential to be used following injury to enhance movement and address motor impairments to a greater extent than is currently promoted. Research in musculoskeletal populations is required.